Revisiting radial velocity measurements of the K2-18 system with the line-by-line framework. Issue 4 (21st October 2022) - Radica, Michael; Artigau, Étienne; Lafreniére, David; Cadieux, Charles; Cook, Neil J; Doyon, René; Amado, Pedro J; Caballero, José A; Henning, Thomas; Quirrenbach, Andreas; Reiners, Ansgar; Ribas, Ignasi
ABSTRACT: The cross-correlation function and template matching techniques have dominated the world of precision radial velocities for many years. Recently, a new technique, named line-by-line, has been developed as an outlier resistant way to efficiently extract radial velocity content from high resolution spectra. We apply this new method to archival HARPS and CARMENES data sets of the K2-18 system. After reprocessing the HARPS data set with the line-by-line framework, we are able to replicate the findings of previous studies. Furthermore, by splitting the full wavelength range into sub-domains, we were able to identify a systematic chromatic correlation of the radial velocities in the reprocessed CARMENES data set. After post-processing the radial velocities to remove this correlation, as well as rejecting some outlier nights, we robustly uncover the signal of both K2-18 b and K2-18 c, with masses that agree with those found from our analysis of the HARPS data set. We then combine both the HARPS and CARMENES velocities to refine the parameters of both planets, notably resulting in a revised mass and period for K2-18 c of 6.99^+0.96_-0.99 M_ and 9.2072 ± 0.0065 d, respectively. Our work thoroughly demonstrates the power of the line-by-line technique for the extraction of precision radial velocity information.